2016
DOI: 10.1111/mec.13802
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of the photoperiodic response and clinal distribution of period alleles in Nasonia vitripennis

Abstract: In seasonal environments, organisms synchronize their life cycle with the annual cycle of environmental factors. In many insect species, this includes a diapause response: a timed dormant stage that allows to survive harsh winter conditions. Previously, we have shown that larval diapause in the parasitic wasp Nasonia vitripennis is induced by the mother upon exposure to a threshold number of short photoperiods (named switch point) and diapause response follows a latitudinal cline in natural populations. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 45 publications
5
39
0
Order By: Relevance
“…Recent studies in two other insects show that per alleles are associated with polymorphism in the timing of 253 autumnal initiation of diapause (critical photoperiod for entrance) (68,69). Genetic changes at per may 254 therefore provide the capacity to adjust diapause transition times across two different seasons, enabling 255 insects to synchronize with both the end and beginning of winter.…”
mentioning
confidence: 99%
“…Recent studies in two other insects show that per alleles are associated with polymorphism in the timing of 253 autumnal initiation of diapause (critical photoperiod for entrance) (68,69). Genetic changes at per may 254 therefore provide the capacity to adjust diapause transition times across two different seasons, enabling 255 insects to synchronize with both the end and beginning of winter.…”
mentioning
confidence: 99%
“…Earlier studies indicate that the male plays a more important role in the determination of diapause in its progeny, for example, in several species of Lepido ptera (Ikten et al, 2011;Chen et al, 2012;Xia et al, 2012;Huang et al, 2013;Fu et al, 2015;Xiao et al, 2015;Pruisscher et al, 2017). In some other insects in other orders, however, females have the same (Paolucci et al, 2016) or an even stronger (Kuang et al, 2011;Chen et al, 2014;French et al, 2014) infl uence than males on diapause in their progeny. In some cases, the relative importance of male and female parents depends on the parameter of diapause studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the face fl y, Musca autumnalis De Geer (Kim et al, 1995) and fl esh fl y Sarcophaga similis Meade (Goto, 2009) diapause is only partially dominant. Finally, in some of the insects studied, the percentage of diapausing individuals in F 1 hybrids is close to the average between those of their parents (Kuang et al, 2011;Söderlind & Nylin, 2011;Chen et al, 2014;Paolucci et al, 2016). The degree of dominance of diapause can differ markedly even in closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the circadian clock gene timeless was found to be in control of diapause incidence (Sandrelli et al, ) and allele frequencies of timeless alleles differentially affecting diapause induction behaviour were shown to covary over latitude (Tauber et al, ) in Drosophila . This pattern, a functional role of one or several circadian clock genes in the control of diapause induction and associated cline in allele frequencies for these genes in natural populations is recurrently observed, e.g., for the parasitic wasp Nasonia vitripennis ( period, cycle and cryptochrome ; Paolucci, Salis, Vermeulen, Beukeboom, & Zande, ) or more recently for the speckled wood butterfly ( period & timeless ; Pruisscher, Nylin, Gotthard, & Wheat, ). However, Emerson, Dake, Bradshaw, and Holzapfel () found that the photoperiodic seasonal clock in control of diapause can evolve independently from the circadian clock.…”
Section: Introductionmentioning
confidence: 95%